Estudo do potencial terapêutico do ácido caféico em protocolos de diabetes e dislipidemia em camundongos - Araújo, Vivianne Machado de (2014)
The diabetes and dyslipidemia are important in cardiovascular risk factors. When associated with oxidative stress may accelerate coronary artery disease and progression of atherosclerotic lesions. There are several natural products that stand out as potential therapeutic agents for treatment of such diseases, including caffeic acid, a phenolic compound that has a variety of biological and pharmacological activities described in the literature. Thus, the aim of this study was to evaluate the therapeutic potential of caffeic acid in experimental protocols of diabetes and dyslipidemia, as well as examine their modulating activity under oxidative stress. Hyperlipidemia was induced in male mice using two protocols by means of a single intraperitoneal administration of 400mg/kg Triton WR-1339 and 400mg/kg Poloxamer-407 in all animals, except for the normal control. The treated groups received doses caffeic acid 25 (CA25), 50 (CA50) and 100 mg/kg (CA100). The serum of these animals was analyzed on two different time intervals for total cholesterol, triglycerides and glucose. Liver tissue was analyzed after both protocols dyslipidemia for products of lipid peroxidation, the non-protein sulfhydryl groups (NP-SH) and the antioxidant enzyme superoxide dismutase (SOD). The hypoglycemic activity of caffeic acid was checked by the protocol of diabetes induced by alloxan. Treatment with three doses of caffeic acid and 200mg/Kg fenofibrate significantly reduced total cholesterol and triglyceride levels 24 and 48 hours after induction of dyslipidemia in both protocols dslipidemia. There was also reduced blood glucose at all doses used to induce dyslipidemia with Poloxamer -407. Furthermore, the treatment caused a reduction in the CA and an increase in lipid peroxidation levels of NP -SH in two models of dyslipidemia and in addition, increased levels of SOD-induced hyperlipidemia in Poloxamer-407. Regarding the induction protocol with alloxan diabetes, there was reduction in blood glucose and total cholesterol levels in the three groups treated with caffeic acid. Triglyceride levels were significantly reduced in animals in groups CA25 and CA100. The results suggest that caffeic acid has a beneficial effect in the treatment of dyslipidemia and diabetes, as well as an important antioxidant activity without the presence of adverse effects. However, most studies of chronic so they can ensure the safety and efficacy of its use are needed.